Individual differences in motives, preferences, and pathology in video games: the gaming attitudes, motives, and experiences scales (GAMES) - Hilgard, Joseph; Engelhardt, Christopher R.; Bartholow, Bruce D. (Frontiers in Psychology, 2013)
A new measure of individual habits and preferences in video game use is developed in order to better study the risk factors of pathological game use (i.e., excessively frequent or prolonged use, sometimes called “game addiction”). This measure was distributed to internet message boards for game enthusiasts and to college undergraduates. An exploratory factor analysis identified 9 factors: Story, Violent Catharsis, Violent Reward, Social Interaction, Escapism, Loss-Sensitivity, Customization, Grinding, and Autonomy. These factors demonstrated excellent fit in a subsequent confirmatory factor analysis, and, importantly, were found to reliably discriminate between inter-individual game preferences (e.g., Super Mario Brothers as compared to Call of Duty). Moreover, three factors were significantly related to pathological game use: the use of games to escape daily life, the use of games as a social outlet, and positive attitudes towards the steady accumulation of in-game rewards. The current research identifies individual preferences and motives relevant to understanding video game players’ evaluations of different games and risk factors for pathological video game use.